If \(2X + 3Y = 12\) , what is \(X\) ?

1) \(X = 6 - (\frac{3}{2})Y\)

2) \(Y = 4 - (\frac{3}{2})X\)

Why is statement 1 not sufficient?

Can I not find the value of Y and substitute in \(2X + 3Y = 12\). I did this, please tell me what mistake I am making

\(2X = 12-3Y\)

From Statement 1 \(X = 6 - (\frac{3}{2})Y\)

Which can be simplified to \(X = (\frac{9}{2})Y\)

Therefore, \(Y = (\frac{2}{9})X\)

Now if i can substitute this Y in \(2X = 12-3Y\)

\(2X = 12-\frac{6}{9}X\)

\(2X = 12-\frac{2}{3}X\)

\(2X+\frac{2}{3}X = 12\)

\(\frac{8X}{3} = 12\)

\(8X = 36\)

\(X = \frac{36}{8}\)

_________________

My First Blog on my GMAT Journey

Arise, Awake and Stop not till the goal is reached